THE EFFECT OF USING FLASH CARD AND PICTURE STORY IN VOCABULARY MASTERY TO THE SEVENTH GRADER OF SMP PGRI 1 MARGATIGA - Khoirul Hidayat (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2016)
Based on the content standard, junior high school students are hoped to master vocabulary about 1000 words, so they can understand the conversation. But it fact, most of the students in junior high school do not master vocabulary well. So, the teacher should be able to choose a good media to help students to increase their vocabulary. In this case, flash card with picture story is two of media that can be used to transfer vocabulary material for the students. The objective of this research is to find the significant differences of using flash card with picture story in vocabulary, and to find which medium is more effective to use as media in vocabulary. This research was true experiment design. Pre test and post test were use to collect the data. There are two problems of the study, (1) are there any significant differences between flash card with picture story in vocabulary mastery for the seventh grade students in SMP PGRI 2 Margatiga academic years 2013/2014?, (2) which one is more effective media in vocabulary learning process, is it flash card or picture story at seventh grade of SMP PGRI 2 Margatiga, academic years 2013/2014?. As a source of data, the researcher utilized flash card with picture story to teach vocabulary for the students. The media help students to learn vocabulary easier and more interesting to understand the subject, so their vocabulary would increase. The result of the research, it was found that the mean score of picture story in pre test is 53,86, in treatment is 81, and in post test 85,33. Meanwhile the mean score of the flash card media in pre test 59,33, in treatment is 73,5, and in post test is 80,66. It means that the student’s vocabulary has increased, and there is significant difference of using picture story and flash card in vocabulary instruction, and picture story was more effective to use in vocabulary instruction.